Batch dialysis of phosphoric acid. Quantification of acid and water transport through Fumasep-FAD membrane - Palatý, Zdeněk; Bendová, Helena (Elsevier Science BV, 2019)
Diffusion dialysis of model aqueous solutions of phosphoric acid was investigated in a two-compartment batch cell equipped with an anion-exchange membrane Fumasep-FAD. The transport of acid through the membrane was accompanied by a significant water transport in the same direction. In order to quantify both these phenomena, the permeability coefficient of the membrane for acid and proportionality coefficient between the flux of water and that of acid were determined from the experimental dependences of acid concentrations and liquid volumes in both the compartments upon time. This study proved that the membrane used is highly permeable for phosphoric acid, i.e., the permeability coefficient was found to be in the range from 0.67 x 10(-5) to 3.25 x 10(-5) m s(-1). Moreover, water transport can satisfactorily be quantified by only one proportionality coefficient with the value of 7.11.
Vsádková dialýza kyseliny fosforečné. Kvantifikace transportu kyseliny a vody membránou Fumasep-FAD
Keywords: Diffusion dialysis; Anion-exchange membrane; Phosphoric acid; Batch cell; Water transport; Difuzní dialýza; Aniontově výměnná membrána; Kyseliny fosforečná; Vsádková cela; Transport vody